"Reuniting what never should have been separated" the Arts and Crafts movement, modernism, and sculpture in Britain 1890 - 1914 - Turner, Sarah Victoria (2015)
Returning to writings about sculpture at the turn of the 20th century, this essay asserts that sculpture is a particularly effective medium through which to reaffirm the very real bonds that connected artistic practices in the decades on either side of 1900. It explores the ways in which the critical vocabulary developed for sculpture in the late 19th century prepared the way for the reception of sculptural experiments of the early 20th century, arguing for a more flexible narrative for sculpture, which can accommodate both objects and critical writings from before and after 1900.
Keywords: Geschichte 1890-1914; Arts and crafts movement; Plastik; Großbritannien